Reading Scripture canonically : theological instincts for Old Testament interpretation - Gignilliat, Mark S. (Grand Rapids, MI, Baker Academic, 2019)
Reading Scripture closely requires more than historical tools, says Gignilliat; it requires recognition of the living God's promised presence through the Bible. He takes seriously the gains of historical criticism, while insisting that the Bible be interpreted as Christian Scripture, offering students a "third way" that assigns proper proportion to both historical and theological concerns. Reading Scripture faithfully requires a set of theological instincts that keep together the close reading of the language of Scripture with Scripture's reason for being and principal subject matter: the Triune God revealed in the person and work of Christ. Gignilliat demonstrates how interpreting the Bible canonically bears exegetical fruit, enabling students to read and engage Holy Scripture as a living witness. - Publisher
Veteran Old Testament teacher Mark Gignilliat explores the theological and hermeneutical instincts that are necessary for reading, understanding, and communicating Scripture faithfully. He takes seriously the gains of historical criticism while insisting that the Bible must be interpreted as Christian Scripture, offering students a "third way" that assigns proper proportion to both historical and theological concerns. Reading and engaging Scripture requires not only historical tools, Gignilliat says, but also recognition of the living God's promised presence through the Bible
Includes bibliographical references and indexes
Keywords: Bible -- Canonical criticism; Bible -- Criticism, interpretation, etc; Bible. -- Hermeneutics